Surgical Strategy to Reduce the Recurrence of Adventitial Cystic Disease after Treatment - Lim, Ji-Ha (Vasc Specialist Int, 2019)
PURPOSE: Adventitial cystic disease (ACD) is a rare condition that causes intermittent claudication and non-atherosclerotic disease without cardiovascular risk factors. The etiology and optimal treatment of ACD remain controversial. The purpose of this study was to analyze surgical treatment results for ACD and to elucidate optimal treatment options. MATERIALS AND METHODS: We retrospectively reviewed 30 patients with ACD who underwent surgery from 2006 to 2018. Twenty-two patients had arterial ACD, six had venous ACD, and two had combined venous and arterial ACD. We reviewed demographic and clinical characteristics, treatment details, and procedure outcomes. RESULTS: Recurrence occurred in 6 cases either after cyst excision alone (4/17) or patch angioplasty (2/2). There was no recurrence after vessel excision with interposition grafting (0/7). Therefore, vessel excision was a statistically significant factor in recurrence prevention (P=0.026). Among the six recurrences, joint connections of the cystic lesions were found in four of the six (66.7%). CONCLUSION: As a curative surgery for ACD, vessel excision with interposition grafting is a better strategy to prevent recurrence than simple cyst excision alone.